PERAN IBU SEBAGAI MANAJER DALAM MEMBENTUK KARAKTER ANAK PERSPEKTIF ISLAM - lina, nur (PSW, 2016)
This paper discusses the role of a mother to a child character formation, through the manager parenting a mother by an Islamic perspective. If a mother is able to manage a good upbringing Islam based on his, then the mother will print good character generation anyway. Because mothers are the foundation for the next-generation, successor on the shoulders of the decidings his bleak and brilliant generations to be born. Â Mother is a perfect man. And will be the perfect man when able to carry out the mandate of God, that became a teacher for their children, caregivers for family, a companion for her husband and was able to arrange household welfare. He was mentor and motivator in the family. His words were able to foster a spirit. His counsel can reduce outburst. Her prayer penetrates to the seventh heaven. Mother who has a very important role in creating a future generation. Thats why the mother is the primary educator and the first on his, , Then the role of a mother is essential